Families with Internationally Adopted Children in Finland: A Study of Emotional Availability in the Early Interaction - Kuusela, Katarina L.; Raaska, Hanna; Elovainio, Marko J.; Heikkilä, Anna-Riitta; Hakulinen, Christian A.; Flykt, Marjo S.; Lapinleimu, Helena (SPRINGER, 2025)
A well-functioning parent-child relationship is crucial for the child's psychological development. We examined the Emotional Availability (EA) in the early interaction of internationally adopted children with their mothers. We also studied whether the quality of the interaction was associated with the sex of the adopted children, the age at the time of adoption, the time they had spent in the family and parental depressive symptoms. The study sample was part of the Finnish Adoption (FinAdo) study and included 79 children (mean age at adoption = 2.58 years, SD = 1.51 months, 37% girls) and their adoptive mothers in Finland. The mother-child interactions were examined with Emotional Availability Scales (EAS) during the first months after adoption (mean = 6.3 months). Our results showed that the overall EA scores were relatively high (mean 4.78-6.18), although the mean levels of parent sensitivity, parent non-intrusiveness, child responsiveness and child involvement were under the high zone of the EA (< 5.5). Children adopted at a younger age and boys received lower scores in the interaction analysis. Our results suggest that families with internationally adopted children seem to be able to create a well-functioning early relationship between the mother and the child.